2022
DOI: 10.3390/info13020066
|View full text |Cite
|
Sign up to set email alerts
|

Post-Editese in Literary Translations

Abstract: In the present study, we investigated the post-editese phenomenon, i.e., the unique features that set machine translated post-edited texts apart from human-translated texts. We used two literary texts, namely, the English children’s novel by Lewis Carroll Alice’s Adventures in Wonderland (AW) and Paula Hawkins’ popular book The Girl on the Train (TGOTT). Both literary texts were Google translated from English into Brazilian Portuguese to investigate whether the post-editese features can be found on the surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…A small number of the participants reported negatively about some aspects, such as the lack of accuracy, the use of literal translation, and unnatural subtitles. We believe that this feedback might be explained in part by the PE proximity to the MT output, which may have resulted in the distortion of the writers' style and have influenced the final product, as reported by Castilho and Resende (2022). In addition, the MTPE subtitles might have contained those problems as a result of the post-editor's and proofreader's lack of experience and formal training in this field.…”
Section: Final Remarksmentioning
confidence: 93%
See 1 more Smart Citation
“…A small number of the participants reported negatively about some aspects, such as the lack of accuracy, the use of literal translation, and unnatural subtitles. We believe that this feedback might be explained in part by the PE proximity to the MT output, which may have resulted in the distortion of the writers' style and have influenced the final product, as reported by Castilho and Resende (2022). In addition, the MTPE subtitles might have contained those problems as a result of the post-editor's and proofreader's lack of experience and formal training in this field.…”
Section: Final Remarksmentioning
confidence: 93%
“…Furthermore, the perception of literal translation could also be explained by the priming effect of the raw MT output on the post-editor's lexical and syntactic choices. In a study conducted on the PE of literary texts, Castilho and Resende (2022) found out that the PE proximity to the MT output may result in the writers' style being distorted and the final product being influenced. In addition to that, an investigation conducted by Toral (2019) about the manifestation of translationese and post-editese found that post-edited texts tend to be simpler and have a higher degree of interference from the source language when compared to human translation.…”
Section: Percentagementioning
confidence: 99%
“…Es decir, condicionan su decisión de traducir de una forma u otra y provocan en última instancia que la variedad léxica de las posediciones sea menor que la de las traducciones humanas. En otras palabras, estos datos refuerzan la idea de que el uso de la traducción automática deja una huella en la traducción final (Toral, 2019;Castilho y Resende, 2022).…”
Section: Sustantivosunclassified
“…This is because neural networks need a lot of data to learn the patterns in Language. The neural method has resulted in more significant improvements in MT quality [44].…”
Section: H Transfer-based Machine Translationmentioning
confidence: 99%